Utility of serum complement factors C3 and C4 as biomarkers during therapeutic management of giant cell arteritis - Conticini, Edoardo; Hellmich, Bernhard; Frediani, B; Csernok, E; Löffler, Christian (Scandinavian journal of rheumatology, 2023)
There is a strong unmet need for biomarkers in giant cell arteritis (GCA), as C-reactive protein (CRP) may be unreliable in patients treated with Tocilizumab (TCZ). We aimed to assess whether C3 and C4 are useful biomarkers in GCA patients, particularly in those treated with TCZ. We retrospectively enrolled all patients who underwent C3 and C4 measurement at baseline. All patients were evaluated at 3, 6, 12, and 24 months after diagnosis, as part of routine follow-up. Two assessments after the end of the observational period, in case of further relapses, were also included. At baseline, mean ± sd levels (mg/dL) of C3 (133 ± 28.99) and C4 (25.9 ± 9.04) were within normal ranges. During follow-up, C3 and C4 decreased in patients attaining remission (107.07 ± 19.86, p = 0.0006; 19.86 ± 10.27, p = 0.01, respectively) and sustained remission (95.85 ± 18.04, p = 0.001; 15.61 ± 9.75, p = 0.006). In TCZ-treated patients, even stronger decreases in C3 (83.11 ± 19.66, p = 0.001) and C4 (8.26 ± 3.83, p < 0.0001) were observed, and their values were not correlated with CRP or erythrocyte sedimentation rate. C3 and C4 do not seem useful in the diagnosis of GCA, as normal values do not rule out active vasculitis. However, C3 and C4 correlate with disease activity. As the low C4 levels found in TCZ-treated patients are not correlated with CRP, C4 should be evaluated as a potential biomarker of disease activity and treatment response.
Online veröffentlicht: 06. April 2022
Gesehen am 17.06.2024